- - عبد الله وسام عبد العباس (Journal of Kerbala for Agricultural Sciences, 2015)
A study was prepared to investigate the suitability of water in the Mahmodia - Jeballa - Sowaira sector of Al - Masab Alaam Drain for irrigation. Twelve testing Locations were selected for this purpose. Measuring of the Parameters was Continued from April To Sep. 2014 This study concluded that the salinity of Al - Masab Alaam Drain water is ( 2.94 – 4.78 ) ds.m-1 and not suitable for the sensitive crops . Also these tests show that the values of Sodicity have a limited effect on the Crop growth , and determine the suitability of water for irrigation purposes on different Soils . The results indicate that the testing samples exceed the limits of chloride and magnesium hazards . This might be reduce the crop growth and productivity . While the boron is not presented in this study . The abstracted result of this study refers to the suitability of water for irrigation of non – sensitive crops for salinity .Also the agricultural lands in this area require continues salt leaching.